2020
DOI: 10.1590/1981-6723.29718
|View full text |Cite
|
Sign up to set email alerts
|

Estudio de los parámetros de freído sobre las propiedades fisicoquímicas de una botana hecha de harinas de maíz, chicharo y salvado de avena

Abstract: Resumen El objetivo de este estudio fue evaluar el efecto de la temperatura y tiempo de freído sobre las propiedades fisicoquímicas: porcentaje de humedad, H; cambio neto de color, ΔE; contenido de grasa, G; índices de absorción, IAA; solubilidad en agua, ISA; densidad aparente, DA; y dureza, D, de un alimento frito tipo botana preparado con una mezcla de harinas de maíz nixtamalizado (HMN), harina de chícharo (HC) y salvado de avena (SA), hidratada al 47%. El estudio mostró que DA y H disminuyeron, mientras q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…The analysis of the proximal composition of PF showed that its main constituent is carbohydrates (Table 1). The amount of carbohydrates, lipids, and ashes in PF was similar to that reported in pea seed flour grown in Jalisco, Mexico (Arriola-Guevara et al, 2020). In this area, the climate is warm-subhumid, and its average annual temperature (20.5 °C) is lower (INEGI, 2023) than the Mixteca Alta region.…”
Section: Proximate Compositionsupporting
confidence: 78%
“…The analysis of the proximal composition of PF showed that its main constituent is carbohydrates (Table 1). The amount of carbohydrates, lipids, and ashes in PF was similar to that reported in pea seed flour grown in Jalisco, Mexico (Arriola-Guevara et al, 2020). In this area, the climate is warm-subhumid, and its average annual temperature (20.5 °C) is lower (INEGI, 2023) than the Mixteca Alta region.…”
Section: Proximate Compositionsupporting
confidence: 78%